Serological and molecular detection of parvovirus b19 in children with acute lymphoblastic leukemia. - Abdullah, Iqbal M.; Abdullah, Shatha F.; Al-Jadiry, Mazin F. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Human parvovirus B19 (B19V) is the only human pathogenic parvovirus, It is highly erythrotropic and preferentially replicates in erythroid progenitor cells (EPCs). Recently the effects of B19 infection have been well studied in children with acute lymphoblastic leukemia (ALL). Objective: To detect parvovirus B19 among children with ALL. Methods: A cross sectional study involved forty five patients with ALL (21 patients were newly diagnosed ALL and 24 children who underwent chemotherapy) who were attending department of oncology in Children’s Welfare Teaching Hospital in Baghdad Medical City between December 2012 and April 2013, compared to forty five of apparently healthy children as a control group, age and sex were matched. A serological and molecular detection of parvovirus B19 were done using enzyme linked immunosorbant assay (ELISA) and Real-time PCR. Results: B19-IgM, IgG and DNA were detected in study cases as (15.6%, 40% and 13.3%) compared to control group (4.4%, 13 % and 0%) respectively. B19-IgG and B19-IgM were detected in newly diagnosed cases in (41.7% and 19.05%) as well as in (38.1% and 12. 5%) of cases on chemotherapy respectively, all cases with B19-DNA signals were underwent chemotherapy (25%) with mean viral load of (36x104 copies/ml). Conclusion: children who suffering from ALL are at increased risk of B19 infection. Notable percentage of persistent B19 infection was recorded among children with ALL who are receiving ongoing treatment.